2021
DOI: 10.3390/nano11071662
|View full text |Cite
|
Sign up to set email alerts
|

Standing and Lying Ni(OH)2 Nanosheets on Multilayer Graphene for High-Performance Supercapacitors

Abstract: For conventional synthesis of Ni(OH)2/graphene hybrids, oxygen-containing functional groups should be firstly introduced on graphene to serve as active sites for the anchoring of Ni(OH)2. In this work, a method for growing Ni(OH)2 nanosheets on multilayer graphene (MLG) with molecular connection is developed which does not need any pre-activation treatments. Moreover, Ni(OH)2 nanosheets can be controlled to stand or lie on the surface of MLG. The prepared hybrids were characterized by X-ray diffraction (XRD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…75–1621), meaning that MLG still maintains an integral layer structure of graphite. More characterization of MLG with SEM, TEM, XPS, AFM in our previous publications [32–35] showed that MLG consists of about 10 graphitic layers with a very low oxidation degree. No other peaks are found for all samples, indicating the high purity of these composites.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…75–1621), meaning that MLG still maintains an integral layer structure of graphite. More characterization of MLG with SEM, TEM, XPS, AFM in our previous publications [32–35] showed that MLG consists of about 10 graphitic layers with a very low oxidation degree. No other peaks are found for all samples, indicating the high purity of these composites.…”
Section: Resultsmentioning
confidence: 91%
“…The crystalline phases of UL-Fe 2 O 3 /MLG samples were analyzed by XRD. As shown in Figure 1, the peaks at 24 [32][33][34][35] showed that MLG consists of about 10 graphitic layers with a very low oxidation degree. No other peaks are found for all samples, indicating the high purity of these composites.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…38,39 Nickel nanoparticles and their oxides have emerged as efficient catalysts in hydrogenolysis, 40,41 dehydrogenation, 42 condensation reactions, 43,44 reduction reactions, 45 and C-C bond formation. [46][47][48] A perusal of the literature reveals that Ni(OH) 2 NPs have been used in the field of electrocatalysis, [49][50][51][52][53] photocatalysis, [54][55][56][57] supercapacitors, [58][59][60][61] and heterogeneous catalysis, [62][63][64] yet Ni(OH) 2 NPs remain relatively less explored in the arena of catalysis. Unsupported Ni(OH) 2 NPs exhibit a tendency to agglomerate.…”
Section: Introductionmentioning
confidence: 99%